Khảo nghiệm một số giống cây ăn trái có triển vọng tại tỉnh Bà Rịa-Vũng Tàu - Lê, Tuấn Quốc (2011)
Tác giả: Lê Tuấn Quốc, ThS; Phạm Thị Chín; Phạm Thị Thúy Yến; Nguyễn Xuân Vinh; Phạm Văn Ngà -- Từ khóa: Cây ăn quả; Xoài; Bưởi; Nhãn; Sầu riêng; Bà Rịa-Vũng Tàu